SPARC expression in tumor microenvironment induces partial epithelial‐to‐mesenchymal transition of esophageal adenocarcinoma cells via cooperating with TGF‐β signaling. (13th October 2022) - Ma, Wen; Yan, Yanli; Bai, Shuheng; Zhou, Yun; Wang, Xuan; Feng, Zhaode; Li, Guangzu; Zhou, Shuling; Zhang, Jiangzhou; Ren, Juan
Abstract: Secreted protein, acidic and rich in cysteine (SPARC) has been characterized as an oncoprotein in esophageal squamous cell carcinoma (ESCC), but its involvement in the pathological development of esophageal adenocarcinoma (ESAD) remains poorly understood. In this study, we aimed to explore the sources of SPARC in the tumor microenvironment (TME) and its functional role in ESAD. Bioinformatic analysis was conducted using data from The Cancer Genome Atlas (TCGA)‐esophageal cancer (ESCA) and Genotype‐Tissue Expression (GTEx). ESAD tumor cell line OE33 and OE19 cells were used as in vitro cell models. Results showed that SPARC upregulation was associated with unfavorable disease‐specific survival (DSS) in ESAD. ESAD tumor cells (OE33 and OE19) had no detectable SPARC protein expression. In contrast, IHC staining in ESAD tumor tissues suggested that peritumoral stromal cells (tumor‐associated fibroblasts and macrophages) were the dominant SPARC source in TME. Exogenous SPARC induced partial epithelial‐to‐mesenchymal transition of ESAD cells, reflected by reduced CDH1 and elevated ZEB1/VIM expression at both mRNA and protein levels. Besides, exogenous SPARC enhanced tumor cell invasion. When TGFBR2 expression was inhibited, the activation of TGF‐β signaling induced by exogenous SPARC was impaired. However, the activating effects were rescued by overexpressing mutant TGFBR2 resistant to the shRNA sequence. Copresence of exogenous SPARC and TGF‐β1 induced higher expression of mesenchymal markers and enhanced the invading capability of ESAD cells than TGF‐β1 alone. In conclusion, this study suggests a potential cross‐talk between ESAD tumor stromal cells and cancer cells via a SPARC‐TGF‐β1 paracrine network.